Can aortic calcium score predict new conduction disturbances in pos-transcatheter aortic valve implantation?. (4th February 2022) - Costa, C; Calvao, J; Amador, A; Proenca, T; Carvalho, M; Pinto, R; Marques, C; Cabrita, A; Grilo, PD; Resende, CX; Torres, S; Sousa, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Transcatheter aortic valve implantation (TAVI) may be the first line treatment for severe aortic stenosis according to overall patient characteristics. Semi-quantitative Agatston score (AS), which quantifies aortic calcium by cardiac computed tomography (CCT), has knowledgeable practical and clinical implications, and is performed in TAVI diagnostic workup. Since conduction disturbances continue to be the most frequent complication, further refinements are required to predict high-risk patients. Purpose: To access if aortic AS relates with new conduction disturbances and permanent pacemaker (PPM) implantation in patients undergoing TAVI. Methods: We retrospectively analyzed all patients who underwent TAVI at a tertiary center from October 2014 to November 2019; patients with previous permanent pacemaker (PPM) or had no aortic AS were excluded. Clinical and electrocardiogram (ECG) data were collected at admission and after the procedure. All categorical variables are reported as numbers and percentages. Continuous variables were analyzed using the two-tailed unpaired Student's t-test and are reported as mean values and the standard deviation. Statistical analysis was performed using the IBM SPSS. Results: 172 patients with a mean age 79 ± 9.1 years old were included (see table 1 for baseline characteristics). AS was on average 3008 ± 2262 (see table 2 for remaining diagnostic workup and procedure characteristics). Comparing AS with new conduction disturbances, no statistically significant difference was found for new complete left branch block (LBBB) (no vs new LBBB, AS: 3179 ± 2555 vs 2637 ± 1388, p= 0, 15) and with new complete atrioventricular block (AVB) (no vs new AVB, AS: 2834 ± 1520 vs 4485 ± 5285, p = 0.2). Considering PPM implantation after TAVI, there was a tendency for higher AS and PPM implantation (no vs PPM implantation, AS: 2756 ± 1451 vs 4242 ± 4310, p = 0.07). In patients who had pre-ballooning, there was no difference relating to AS; however, in patients who had no pre-ballooning there was a trend to higher AS and PPM implantation (no vs PPM implantation, AS: 2417 ± 1301 vs 4616 ± 4969, p = 0.06). No statistically significant difference was found when comparing earlier (Portico, CoreValve Evolut R) vs newer valves (CoreValve Evolut Pro; Edward Sapiens 3; Accurate Neo). Conclusion: Aortic calcium measured by Agatston score did not show a correlation with new LBBB or new AVB after TAVI. Nevertheless, it seems to be a trend for higher AS and PPM implantation; this was more noticeable when pre-ballooning was not performed. Further studies are needed in order to further elucidate this association.